1998
DOI: 10.1161/01.cir.98.11.1071
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cardiovascular Variability in Obstructive Sleep Apnea

Abstract: Cardiovascular variability is altered in patients with OSA. This alteration is evident even in the absence of hypertension, heart failure, or other disease states and may be linked to the severity of OSA. Abnormalities in cardiovascular variability may be implicated in the subsequent development of overt cardiovascular disease in patients with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
331
3
34

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 509 publications
(390 citation statements)
references
References 49 publications
22
331
3
34
Order By: Relevance
“…Simultaneous assessment of BRS and HRV according to sleep microstructure could prove helpful in identifying patients at increased risk for nocturnal events (eg, early postmyocardial infarction, impaired left ventricular function, obstructive sleep apnea syndrome) 37 and in guiding therapy effectively during the nighttime. 1 This would be possible with a complete, noninvasive, minimally disturbing approach.…”
Section: Perspectivesmentioning
confidence: 99%
“…Simultaneous assessment of BRS and HRV according to sleep microstructure could prove helpful in identifying patients at increased risk for nocturnal events (eg, early postmyocardial infarction, impaired left ventricular function, obstructive sleep apnea syndrome) 37 and in guiding therapy effectively during the nighttime. 1 This would be possible with a complete, noninvasive, minimally disturbing approach.…”
Section: Perspectivesmentioning
confidence: 99%
“…Following obstructive apneas and hypopneas, there is an increase in sympathetic activity resulting in peripheral vasoconstriction and increased HR, which persists during the daytime (33). It has been hypothesized that the increased transmural gradients across the atria, ventricles and aorta, which may disrupt ventricular function and result from changes in intrathoracic pressure during obstructive events, lead to autonomic and hemodynamic instability (32).…”
Section: Repetitive Respiratory Events In Childrenmentioning
confidence: 99%
“…This cycle may repeat itself hundreds of time during sleep, thus inducing an overall effect of nighttime sympathetic-excitation and surges of blood pressure, responsible for the "non-dipping" profile of blood pressure. However, one of the most remarkable characteristics of OSA is the presence of an heightened sympathetic activity also during wakefulness, as demonstrated by MSNA recordings (3,26) and spectral analysis of HRV (27). The mechanisms implicated in this phenomenon are still unclear.…”
Section: Sleep Breathing Disorders and Ansmentioning
confidence: 99%
“…Firstly, it has been hypothesized that the effect of sympathetic excitation induced by hypoxia might persist for a long time, also during normo-oxygenation conditions (28,29). Secondly, a potentiation of peripheral chemo-reflex responses has been detected in OSA subjects, possibly contributing to maintain a tonic sympathetic excitation during wakefulness (27,30). Lastly, a depressed baro-reflex sensitivity (BRS) was reported, although most studies assessed baroreceptor responses only during sleep (31)(32)(33)(34) while those reporting wakefulness data concluded that BRS was unchanged (35,36) (Figure 3).…”
Section: Sleep Breathing Disorders and Ansmentioning
confidence: 99%